Simple Method for the Isolation of Encephalomyocarditis Virus Ribonucleic Acid - Kerr, I. M. (1972)
A simple purification procedure for encephalomyocarditis virus is described, yielding material suitable for extraction of viral ribonucleic acid for use as messenger in animal cell-free systems.